The greening of pharmaceutical engineering practice, analysis, and methodology - Islam, Rafiqul 1959- (Wiley-Scrivener, 2016)
"The pharmaceutical industry is one of the most important industries in the world, offering new medicines, vaccines, and cures to a global population. It is a massive industry, worthy of a deep and thorough examination of its processes and chemistry, with a view toward sustainability. The authors describe what is and isn't truly sustainable, offering a new approach and a new definition of the sustainability of pharmaceutical and chemical engineering and the science behind it. This is a cutting-edge work, aimed at engineers, scientists, researchers, chemists, and students"--